Bone Tuberculosis: Clinical Profile of 40 Patients in Dr. Soetomo General Hospital Surabaya - Yonatan Esli Alexander Tidja; Sjahjenny Mustokoweni; Tania Ardiani Saleh (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Bone and joint tuberculosis are specific infection inflammation of Mycobacterium tuberculosis, mostly affected bone and joint confirmed by acceleration of vascular supply to vertebrae and growth line of long bone. The aim of this study is to know clinical profile of bone and joint tuberculosis’ patients. Methods: This study was conducted using descriptive observational method, samples were tested by observation descriptive test. Results: The average ages of bone and joint tuberculosis hospitalized patients of RSUD Dr. Soetomo Surabaya are 35-44 years. There are 22 cases on male (55%) and 18 cases on female (45%) with 29 subjects of Hb’s abnormal number (72.5%), 15 subjects of abnormal leucocytes (37.5%), 20 subjects of abnormal thrombocyte (50%), 34 subjects of abnormal ESR (94.4%), 20 patients of abnormal C-reactive protein (54.1%), 11 subjects of abnormal serum creatinine (28.9%), 13 subjects of abnormal sodium level (35.1%), 15 patients of abnormal potassium level (40.5%), and 16 patients of abnormal chloride level (43.2%). There are 16 subjects with smoking history (40%), 29 subjects of positive tuberculosis history (72.5%), 6 subjects with positive tuberculosis family history (15%), 30 subjects of pain as main problems (75%), 5 subjects of swelling or pus as main problems (12.5%), 5 subjects of extremities disability as main problems (12.5%). Dominant location of infection is vertebrae (95%) which are suffered by 38 subjects with thoracal as the main level of infection, suffered by 15 subjects (50%). Other levels of infection are lumbal with 12 subjects (40%), cervical with 3 subjects (10%), and pelvis or thigh with 2 subjects (5%). Conclusion: From 40 subjects, bone and joint tuberculosis mostly suffered by elderly, male risks more than female. Most of hematology tests results were abnormal. Most subjects suffered abnormal C-reactive protein. Most subjects’ hematology tests were BUN, creatinine serum, and electrolyte normal. Number of subjects with smoking habits was dominant. Most subjects were having tuberculosis history but negative family history. Most subjects complained about pain with vertebrae level thoracal as dominant location of infection.